The Noisy Silence of Gukurahundi: Truth, Recognition and Belonging - Alexander, Jocelyn (Journal of southern African studies, 2021)
A period of terrible state repression known as 'Gukurahundi' indelibly marked the foundational years of the Zimbabwean nation. The perpetrators of that period still hold power. It has never been subject to an official truth-telling process, nor have the responsible actors been held accountable. Instead, irreconcilable narratives about this past have interacted and, for those subjected to violence, proliferated, producing what I call a 'noisy silence' at the edges of the nation. This noise rumbles on because of a perpetual failure of public recognition of the violent past, but it does so in highly varied ways and to distinct purposes. I seek to trace the history of this noisy silence from its start in the irreconcilable narratives of the 1980s, themselves powerfully rooted in earlier liberation struggle ideas and relationships, through subsequent decades. Noisy silence sat in between an official, justificatory account of Gukurahundi on the one hand and the fearful, silenced memories of individuals on the other. It occupied a productive middle ground where collective, creative efforts delineated and demanded new political possibilities and terms of belonging through truth-telling, re-imagined and mourned nations and cross-generational attempts to heal and hold perpetrators to account.